Biochemical research of phenyclidine reseptor : Interaction to specific bonding to the lower affinity receptor - Gusdinar, Tutus; Chicheportiche, Robert (Indonesian Journal of Pharmacy, 2007)
Fixed concentration of MK-801 molecule had been used as a specific ligand for differenciating two kinds of phencyclidine (PCP) and thienylphencyclidine (TCP) receptors. By using several drug molecules which have different pharmacological action, as well as such molecular affinity (IC50) to the rat brain, it was obtained that both of these interacting receptors had equal character for its higher or lower affinity sites. The MK-801 molecule inhibited much strongly (IC50 is about 10 nM) fixation of 3HTCP to its higher affinity receptor and much weakly (IC50 is about 10 μM) fixation of 3H-PCP to its lower affinity receptor. The MK-801 molecule could be used as well for differenciating two 3H-TCP receptors, the higher and the lower affinity.Key words : phencyclidine – thienylphencyclidine – MK-801 – higher affinity receptor– lower affinity receptor.